Whey permeate containing galacto-oligosaccharides as a medium for biomass production and spray drying of Lactobacillus plantarum CIDCA 83114. (June 2016) - Hugo, Ayelén A.; Bruno, Florencia; Golowczyc, Marina A.
Abstract: Whey permeate (WP) is a low-cost waste product that can be used as a growth media of probiotic bacteria and as a source of galacto-oligosaccharides (GOS) being an excellent alternative to obtain probiotic biomass in a more economical way. The aim of this work was to evaluate the suitability of using WP and WP enriched with GOS (WP-GOS) as a culture broth and as a carrier for probiotic Lactobacillus plantarum CIDCA 83114 to obtain viable dehydrated bacteria using spray drying. This strain was able to grow satisfactorily in unsupplemented WP showing a similar behavior in WP and WP-GOS. It also performed well in spray drying. Viability of dehydrated lactobacilli was monitored throughout the storage of powders at 20 °C for 10 weeks. Survival during storage of L. plantarum grown and dehydrated in WP-GOS was significant higher than strain grown and dehydrated in WP at the end of storage time. Strain grown in WP increased their tolerance to acid conditions and the presence of GOS increased significantly its survival at low pH environment in dehydrated condition. L. plantarum CIDCA 83114 grown and dehydrated in WP-GOS constitute a low-cost spray-dried preparation containing high concentration of viable bacteria with enhanced gastrointestinal passage resistance. Highlights: Lactobacillus plantarum can grow properly in unsupplemented whey permeate (WP) and WP with GOS. L. plantarum can be spray dried from WP to obtain a low-cost spray-dried preparation. L. plantarum from WP-GOS exhibited higher survival rate during storage. Dehydrated probiotic increased significantly its survival at low pH environment.